Islamism and islamic literature in contemporary Turkey: From epic to novel understandings of Islam - Çayır, Kenan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2004., 2004)
This study explores Islamism and Islamic identities through literary representations of Islamism in Turkey in the last two decades, a period in which Islamism came on the public agenda through novels, films, music and other artistic productions. My focus will be in particular on the Islamic novels of the 1980s and 1990s in order to elucidate Islamist actors' perceptions of 'self' and 'other' and of the social milieu in which they lived. I will note a change in emphasis in Islamic representations and discourse between the 1980s and 1990s. I will argue that with their didactic and pedagogical narratives detailing 'how Muslims should live in the modern world,' Islamic novels of 1980s provided Islamists with a means to disseminate ideas in popularized form and to develop life strategies that paved the way for assertive collective Islamic subjectivity. By contrast, in the 1990s more self-reflexive/self-exposing novels have emerged in Islamic circles that mirror the questioning of radical conceptions of the previous decade in Islamic circles. The new Islamic novels, with their self-reflexive forms and their narratives exploring the inner conflicts of Islamic actors in the face of changing social relations challenge the collective definitions of Islamic identity and signify novel practices and interpretations of Islam.
Keywords: Turkish literature -- History and criticism.; Islamic literature, Turkish.